2014
DOI: 10.1038/ncomms5583
|View full text |Cite
|
Sign up to set email alerts
|

Magnetochiral dichroism resonant with electromagnons in a helimagnet

Abstract: Cross-coupling between magnetism and electricity in a solid can be hosted by multiferroics with both magnetic and ferroelectric orders. In multiferroics, the collective spin excitations active for both electric and magnetic fields, termed electromagnons, play a crucial role in the elementary process of magnetoelectric (ME) coupling. Here we report the colossal dynamical (optical) ME effect, or more specifically the magnetochiral (MCh) effect, in the electromagnon resonance for the screw spin helimagnet CuFe 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 44 publications
(83 reference statements)
3
50
1
Order By: Relevance
“…The first one, the so-called magnetochiral dichroism (MChD), requires a chiral material with finite magnetization, and the directional dichroism is present for light beams propagating parallel and antiparallel to the direction of the magnetization. MChD has been detected in several akermanite compounds, [8,11] and in Cu(Fe,Ga)O 2 [12]. The second one is realized when a material simultaneously possesses magnetization, M and electric polarization (or a polar axis), P [19].…”
Section: Pacs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one, the so-called magnetochiral dichroism (MChD), requires a chiral material with finite magnetization, and the directional dichroism is present for light beams propagating parallel and antiparallel to the direction of the magnetization. MChD has been detected in several akermanite compounds, [8,11] and in Cu(Fe,Ga)O 2 [12]. The second one is realized when a material simultaneously possesses magnetization, M and electric polarization (or a polar axis), P [19].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…These functionalities rely on the magneto-electric (ME) effect which is enhanced in multiferroics by the coexistence of ferroelectric and magnetic order. Recent studies of multiferroic materials from gigahertz frequencies to Xray wavelengths have demonstrated that finite frequency ME effect gives rise to another useful phenomenon, the directional dichroism [4][5][6][7][8][9][10][11][12][13][14]. The non-reciprocal directional dichroism and its Kramers-Kronig counterpart, non-reciprocal directional birefringence, are the absorption coefficient and refractive index differences, respectively, for counter-propagating light beams detectable irrespective of the light polarization state.…”
mentioning
confidence: 99%
“…Indeed observations of the directional dichroism have been reported for several multiferroic materials such as Ba 2 CoGe 2 O 7 [17][18][19], RMnO 3 (R =rare-earth ions) [20,21], and CuFe 1−x Ga x O 2 [22], in which nontrivial spin orders induce the ferroelectric polarization via the relativistic spin-orbit interaction. In these materials, the optical ME effect is observed at the electromagnon resonance frequencies in the terahertz (THz) regime.…”
mentioning
confidence: 99%
“…The presence of an external magnetic field within a chiral medium introduces time-reversal as well as space-reversal symmetry breaking simultaneously, and, as a second-order phenomenon, it is very hard to measure experimentally. So far, magnetochirality has been verified in liquid molecular systems, organic compounds, anisotropic crystals and chiral ferromagnets [2][3][4][5][6][7][8][9][10][11][12][13][14]. Recently, it has been theoretically proposed that magnetochiral dichroism (MChD) can be promoted in chiral magnetic metamaterials such as helical lattices of magnetic garnet spheres [15].…”
Section: Introductionmentioning
confidence: 99%